Faktor Risiko Bunuh Diri sebagai Dampak dari Bullying dan Cyberbullying pada Remaja - Noorkholisoh, Lulu; Rahmawati, Elin Maulida; Saripah, Ipah (COUNSELIVE: Jurnal Konseling Kehidupan, 2025)
Bullying and cyberbullying are increasingly recognized as serious risk factors contributing to the rising incidence of suicide among adolescents across various countries. Differences in social and cultural contexts, as well as the extent of digital media use, result in varying prevalence rates of suicide risk associated with such forms of victimization. This study aims to explore the prevalence of suicide risk factors as a consequence of bullying and cyberbullying among adolescents. The research employed a systematic literature review method by examining scholarly articles obtained from databases including Google Scholar, Scopus, Routledge, and Sage Publishing. From a total of 200 articles identified using relevant keywords, seven met the inclusion criteria and were further analyzed. The review findings indicate that the majority of adolescents who experienced bullying and cyberbullying had attempted suicide at least once. Female adolescents exhibited a higher prevalence of suicidal ideation and suicide attempts compared to male adolescents. These findings confirm that bullying, both direct and online, represents a significant risk factor for adolescent mental health. Therefore, preventive efforts through character education, school counseling, and effective protective policies are necessary to reduce the negative impact of bullying on adolescents’ psychological well-being.